ШЕШЕНЛИК ӨНЕРИ ҲƏМ ИМПРОВИЗАЦИЯ - Матимов, К.Г.; Өтепбергенова, Г. (FAN va JAMIYAT, 2020)
The article examines the improvisation of resourcefulness in oratory art in the history of Karakalpak literary. Here, the sources of the emergence of an improvisational literary phenomenom, the stages of formation, the history of development are briefly described. The article deals with wit issues of the art of wit in the heritage of such major representatives of oratory as Jiyrenshe sheshen and Muyten jirau.